Cytochrome P450-derived versus Mitochondrial Oxidant Stress in Acetaminophen Hepatotoxicity - Jaeschke, Hartmut (Toxicol Lett, 2015)
In evaluating the mechanisms of acetaminophen hepatotoxicity in experimental systems, it is critical to keep in mind the relevance of the model system for humans. Important aspects of the human toxicity include formation of a reactive metabolite by the cytochrome P450 system and protein adduct formation, which is thought to trigger mitochondrial dysfunction and oxidant stress ultimately causing necrotic cell death. If models that miss critical parts of this well-established mechanism are used, the relevance of the new information for the human toxicity has to be questioned. Therefore, we feel it is necessary to express our concern regarding the recent publication by Jiang et al. (2015).